ANALISIS KINERJA KEUANGAN PT. MUSTIKA RATU TBK SEBELUM DAN SELAMA PANDEMI COVID 19 - S, Suhendra; Nabila, Nurul (Patria Artha Journal of Accounting dan Financial Reporting, 2023)
This study aims to determine the financial performance of PT Mustika Ratu Tbk before and during the Covid-19 pandemic. Company performance is measured by using financial ratios: liquidity ratio which is analyzed by Current Ratio (CR), activity ratio which is analyzed by total assets turnover (TATO), solvency ratio which is analyzed by debt to equity ratio (DER), and profitability ratio which is analyzed by net profit margin (NPM). This type of research is quantitative research with secondary data analysis. The analytical method in this research is quantitative descriptive analysis method. The results showed that: The results of the research show that: (1) Liquidity Ratio which is analyzed by Current Ratio. Overall, the Financial Performance of PT Mustika Ratu Tbk Based on the Current Ratio "Good" because it is above the industry average and although it has decreased, the performance is still in good condition because it is not far below the ratio standard. (2) Activity ratio analyzed by Total Assets Tumover.